2016
DOI: 10.7150/jca.13403
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D and Colorectal, Breast, and Prostate Cancers: A Review of the Epidemiological Evidence

Abstract: Over the past two decades, the question of whether vitamin D has a role in cancer incidence, progression, and mortality has been studied in detail. Colorectal, breast, and prostate cancers have been a particular area of focus; together, these three malignancies account for approximately 35% of cancer cases and 20% of cancer deaths in the United States, and as such are a major public health concern. Herein, we review and synthesize the epidemiological research regarding vitamin D, as measured by the biomarker 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
97
0
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(103 citation statements)
references
References 115 publications
4
97
0
2
Order By: Relevance
“…Interestingly, 1 recent study found that a higher vitamin D status was more beneficial for colorectal tumors having greater lymphocytic infiltration (138), supporting the view expressed in a recent commentary that substantially greater attention is needed with respect to organ site-specific biological mechanisms (139). The current literature also suggests that there may be other important factors that interact with vitamin D status, such as menopausal status in breast cancer (17), sex in colorectal cancer (140), and circulating vitamin D binding protein in prostate cancer (141). Relevant to the latter observation, studies have begun to pay more attention to the measurement of 25(OH)D by examining the role of free versus total vitamin D in cancer etiology, with free 25(OH)D appearing to be more important for some cancer sites and total 25(OH)D appearing to be more important for others (12,80,(141)(142)(143) (145).…”
Section: Current Expert Recommendations Versus Population Trendssupporting
confidence: 59%
“…Interestingly, 1 recent study found that a higher vitamin D status was more beneficial for colorectal tumors having greater lymphocytic infiltration (138), supporting the view expressed in a recent commentary that substantially greater attention is needed with respect to organ site-specific biological mechanisms (139). The current literature also suggests that there may be other important factors that interact with vitamin D status, such as menopausal status in breast cancer (17), sex in colorectal cancer (140), and circulating vitamin D binding protein in prostate cancer (141). Relevant to the latter observation, studies have begun to pay more attention to the measurement of 25(OH)D by examining the role of free versus total vitamin D in cancer etiology, with free 25(OH)D appearing to be more important for some cancer sites and total 25(OH)D appearing to be more important for others (12,80,(141)(142)(143) (145).…”
Section: Current Expert Recommendations Versus Population Trendssupporting
confidence: 59%
“…Epidemiologic studies by Apperly (1941) identified an inverse correlation between sun exposure and cancer risk in people. This spurred further research, which identified an association between decreased 25-hydroxyvitamin D (25[OH]D) concentrations and an increased risk of certain tumor types such as colonic, prostatic, and mammary cancers (Jacobs et al, 2016). Veterinary researchers have identified an increased overall risk of cancer, mast cell tumor, lymphoma, and malignant hemoabdomen in dogs with significantly lower 25(OH)D (Gerber et al, 2004;Mellanby, 2016;Selting et al, 2016).…”
mentioning
confidence: 99%
“…These guidelines are consistent with recommendations for the prevention of other major diseases as well, and, if followed, are associated with healthier lives overall (42)(43)(44). To our knowledge, no studies have assessed the relation between ACS guidelines for cancer prevention and circulating concentrations of vitamin D metabolites, which are biomarkers often linked to health outcomes (45). This current work offers evidence indicating that greater adherence to an overall lifestyle pattern as outlined by the ACS nutrition and physical activity cancer prevention guidelines is associated with higher concentrations of both 25(OH)D and 1,25(OH) 2 D, based on a pooled sample of participants enrolled in one of 2 chemoprevention trials in Arizona.…”
Section: Discussionmentioning
confidence: 61%